All about Steve - Bullock, Sandra; McLaglen, Mary, 1959-; Barker, Kim.; Traill, Phil, 1973-; Church, Thomas Haden; Cooper, Bradley; Beck, Christophe, 1972-; Fox 2000 Pictures; Radar Pictures; Fortis Films; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2009)
Crossword puzzle constructor Mary Horowitz is smart and pretty, but a disaster that shakes news cameraman Steve to the core. Set up on a blind date with Steve, Mary thinks the chemistry is undeniable and just knows she's found her soulmate. She decides to do anything and go anywhere to be with him. Mary's escalating infatuation is encouraged by the self-serving actions of news reporter Hartman Hughes who enjoys torturing his insolent cameraman at every opportunity. When the overzealous Mary becomes embroiled in the news story of the year, Steve and Hartman begin to see her differently. Despite the media storm surrounding her, Mary's upbeat manner not only brings everyone together but she ends up finding her own oddball friends and discovers her true place in the world.
Director of photography, Tim Suhrstedt ; editor, Virginia Katz ; music, Christophe Beck.
Sandra Bullock, Thomas Haden Church, Bradley Cooper.
MPAA rating: PG-13; for sexual content including innuendos.
DVD, region 1, widescreen (1.85:1); Dolby Digital 5.1 surround.
English, dubbed French or dubbed Spanish dialogue; English or Spanish subtitles; closed-captioned.
Keywords: Crossword puzzle makers -- United States -- Drama; Camera operators -- United States -- Drama; Blind dates -- United States -- Drama; Television journalists -- United States -- Drama; Man-woman relationships -- United States -- Drama; Friendship -- United States -- Drama